Multilaboratory Validation of Rapid Spot Tests for Identification of Escherichia coli - York, Mary K. (American Society for Microbiology, 2000)
To validate the accuracy of rapid tests for identification of Escherichia coli, five laboratories sequentially collected 1,064 fresh, clinically significant strains with core criteria of indole-positive, oxidase-negative, nonspreading organisms on sheep blood agar plates (BAP), having typical gram-negative rod plate morphology, defined as good growth on gram-negative rod-selective media. An algorithm using beta-hemolysis on BAP, lactose reaction on eosin-methylene blue or MacConkey agar, l-pyrrolidonyl-β-naphthylamide (PYR), and 4-methylumbelliferyl-β-d-glucuronide (MUG) was evaluated. Identifications using the algorithm were compared to those obtained using commercial kit system identifications. One thousand strains were E. coli and 64 were not E. coli by kit identifications, which were supplemented with conventional biochemical testing of low probability profiles. Of the 1,064 isolates meeting the core criteria, 294 were beta-hemolytic and did not require further testing to be identified as E. coli. None of the 64 non-E. coli strains were hemolytic, although other indole-positive, lactose-negative species were found to be hemolytic when further strains were examined in a follow-up study. Of the remaining strains, 628 were identified as E. coli by a lactose-positive and PYR-negative reaction. For nonhemolytic, lactose-negative E. coli, PYR was not helpful, but a positive MUG reaction identified 65 of 78 isolates as E. coli. The remaining 13 E. coli strains required kit identifications. This scheme for E. coli identification misidentified three non-E. coli strains as E. coli, for an error rate of 0.3%. A total of 13 kit identifications, 657 PYR tests, and 113 MUG tests were needed to identify 1,000 E. coli strains with the algorithm. The use of this rapid system saves laboratory resources, provides timely identifications, and yields rare misidentifications.